Kebutuhan Suportif Edukatif dalam Manajemen Diri Stres pada Pasien Hipertensi - Sulistiyowati, Ermi Tri; Wulandari Febrian Poma; Maria Suryani (Jurnal Kesehatan Cendikia Jenius, 2024)
Background: Hypertension is a non-communicable disease that is the number one cause of death in the world. Stress in hypertensive patients can worsen the patient's condition and increase the risk of complications. Nurses have an important role to provide educational support in self-management in hypertensive patients. Objective: Knowing the level of educational support needs in stress self-management in hypertensive patients. Research Methods: The research design used in this study was descriptive quantitative. A sample of 40 respondents was taken using the total sampling technique. Data were collected using a stress management questionnaire. Results: All respondents, as many as 40 people (100%), have a low level of educational supportive needs in stress self-management. Conclusion: Respondents need educative support in low stress self-management. Suggestion: Nurses identify the patient's level of educational support needs in managing stress so that they can provide educational support according to the patient's needs.